Optimalisasi Wortel Menjadi Selai Wortel Melalui Teknologi Tepat Guna di Desa Sikunang Kabupaten Wonosobo - Broto, Wisnu; Arifan, Fahmi; Supriyo, Edy; Kartikasari, Nanik; Prasetyo, Alif Nur Fauzi; Utami, Palupi Diah (Sekolah Vokasi Universitas Diponegoro, 2024)
Sikunang Village is one of 16 villages in Kejajar District, Wonosobo Regency, Central Java. Sikunang village with an area of 374 km2. Sikunang Village is referred to as an agropolitan village because of its abundant agricultural potential, especially carrots. Carrots that are ready to harvest are directly sold by farmers to middlemen so there has been no diversification of processed products from carrots that have a higher value. So it takes the creativity of citizens in diversifying processed food products from carrots. One of them is processing carrots into carrot jam using appropriate technology. The problem faced is that the jam cooker is still simple manual so that the doneness of the jam is not evenly distributed and some of the burnt is dark in color and the carrot jam filter has a small capacity so that it still cannot be perfectly smooth for the final result. Therefore, the community service program focuses on training innovations in the use of automatic jam cookers and jam filtration tools. In addition, the program was made with the aim that the Information and Counseling Center (PIK) for Adolescents in Sikunang Village and MSMEs in Sikunang Village can be optimal in producing carrot jam. It is expected that diversification of processed carrot jam food products will increase creativity in processing natural resources independently in the village and the economy of surrounding residents.